2022
DOI: 10.1515/cclm-2022-0873
|View full text |Cite
|
Sign up to set email alerts
|

Positivization time of a COVID-19 rapid antigen self-test predicts SARS-CoV-2 viral load: a proof of concept

Abstract: Objectives This proof of concept study was aimed to validate the hypothesis that the time of positivization of SARS-CoV-2 self-performed rapid diagnostic tests (RDTs) may reflect the actual viral load in the specimen. Methods A SARS-CoV-2 positive sample with high viral load was diluted and concomitantly assayed with molecular assay (Xpert Xpress SARS-CoV-2) and RDT (COVID-VIRO ALL IN RDT). The (mean cycle threshold; Ct) valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Salvagno et al. also examined LFT predicted and measured Ct values in unknown clinical samples and found a correlation coefficient of 0.577, a lower value than we found with both the BN ( r = 0.93) or FF ( r = 0.97) assays 10 . We also found that high viral load samples could be diluted and accurately measured in the two antigen tests, which not only increases the upper range of viral concentrations that can be measured, but additionally allows a longer time frame between applying the samples and the test turning positive.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Salvagno et al. also examined LFT predicted and measured Ct values in unknown clinical samples and found a correlation coefficient of 0.577, a lower value than we found with both the BN ( r = 0.93) or FF ( r = 0.97) assays 10 . We also found that high viral load samples could be diluted and accurately measured in the two antigen tests, which not only increases the upper range of viral concentrations that can be measured, but additionally allows a longer time frame between applying the samples and the test turning positive.…”
Section: Discussioncontrasting
confidence: 77%
“…Salvagno et al also examined LFT predicted and measured Ct values in unknown clinical samples and found a correlation coefficient of 0.577, a lower value than we found with both the BN (r = 0.93) or FF (r = 0.97) assays. 10 We also found that high viral load samples could be diluted and accurately measured in the two antigen tests, which not only increases the upper range of viral concentrations that can be measured, but additionally allows a longer time frame between applying the samples and the test turning positive. This latter factor may increase the accuracy of the timing of when the test turns positive, because we found that measurements at both ends of the working range of the viral dose-response versus time-to-positivity curves are less precise than those in the middle part of the doseresponse curve (data not shown).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations